ANALISIS MOLEKULER ESCHERICHIA COLI SEROTYPE O157:H7 PADA AIR MINUM DALAM KEMASAN DAN ISI ULANG MENGGUNAKAN TEKNIK - Kandou, Febby Ester Fany (CHEMISTRY PROGRESS, 2009)
This research aims to analyze the existence of Escherichia coli serotype O157:H7 in packaged andrefilled drinking water using Polymerase Chain Reaction (PCR) technique with gene target rfbE. Theresearch was carried out at Molecular Biology and Immunology Laboratory of Medical Faculty,Hasanuddin University Makassar. The methode used was Polymerase Chain Reaction (PCR) techniquei.e. Isolation/Extraction DNA bacteria of Escherichia coli serotype O157:H7 with Boom methode,Amplification DNA fragments of bacteria and Electrophoresis for visualization DNA fragments. Theresults show that based on DNA band that resulted, there are 8,33% of packaged drinking watersamples and 25% of refilled drinking water samples are contaminated by Escherichia coli serotypeO157:H7.